Opportunity for All : Promoting Growth and Inclusiveness in the Middle East and North Africa - Purfield, Catriona (Departmental Papers; Departmental Paper ;, 2018)
This publication brings together a set of IMF papers that prepared as backgrounds for the various sessions of the conference and will help put into broader dissemination channels the results of this important conference. An official IMF publication is well disseminated into academic and institutional libraries and book channels. The IMF metadata will also make the conference papers more discoverable online.